Answer:
y=-6 that would be it. remember slope is rise over run
We need to determine the term life insurance amount per thousand on a 22-year-old female for a 5-year policy given that the face value of the policy is $600,000 and the annual premium is $1332.
Since we are supposed to find the term life insurance amount per thousand, therefore, we will use the following formula:
![\text{Term life insurance amount}=\frac{\text{Annual premium}}{\text{Face value of insurance}}*1000](https://tex.z-dn.net/?f=%5Ctext%7BTerm%20life%20insurance%20amount%7D%3D%5Cfrac%7B%5Ctext%7BAnnual%20premium%7D%7D%7B%5Ctext%7BFace%20value%20of%20insurance%7D%7D%2A1000)
Upon substituting the values of annual premium and face value of insurance, we get:
![\text{Term life insurance amount}=\frac{\text{1332}}{\text{600000}}*1000\\ \text{Term life insurance amount}=\$2.22](https://tex.z-dn.net/?f=%5Ctext%7BTerm%20life%20insurance%20amount%7D%3D%5Cfrac%7B%5Ctext%7B1332%7D%7D%7B%5Ctext%7B600000%7D%7D%2A1000%5C%5C%0A%5Ctext%7BTerm%20life%20insurance%20amount%7D%3D%5C%242.22)
Therefore, the required life insurance amount is $2.22.
Answer:
![x+2y=-11](https://tex.z-dn.net/?f=x%2B2y%3D-11)
Step-by-step explanation:
Slope intercept form of a line is given by:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
Where
m is the slope and b is the y-intercept
Given slope is ![-\frac{1}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D)
We can write:
![y=-\frac{1}{2}x+b](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7Dx%2Bb)
Now to find b, we replace x with -3 and y with -4, given, so we have:
![y=-\frac{1}{2}x+b\\-4=-\frac{1}{2}(-3)+b\\-4=\frac{3}{2}+b\\b=-5.5](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7Dx%2Bb%5C%5C-4%3D-%5Cfrac%7B1%7D%7B2%7D%28-3%29%2Bb%5C%5C-4%3D%5Cfrac%7B3%7D%7B2%7D%2Bb%5C%5Cb%3D-5.5)
So, the equation is:
![y=-\frac{1}{2}x-\frac{11}{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B11%7D%7B2%7D)
Now,
The standard form is given by:
![Ax+By=C](https://tex.z-dn.net/?f=Ax%2BBy%3DC)
So, we take x and y to left side and the constant to right side. Rearranging, we get:
![y=-\frac{1}{2}x-\frac{11}{2}\\2y=-x-11\\x+2y=-11](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B11%7D%7B2%7D%5C%5C2y%3D-x-11%5C%5Cx%2B2y%3D-11)
The first answer choice is right.
Hey, I’m pretty sure the answer is y=1/2x + 0.
To explain, we can plug the x value into the equation for all of the x values, and we will get our y value.
So the first one,
y=1/2(1) + 0 —> 1/2
The second one,
y=1/2(2) + 0 —> 1
And so forth, the rest of the equations will be correct. I hope that helps ! :D
Answer:
14,400
Step-by-step explanation:
Hope this helpfull..but if it's not,im so sorry